A SYSTEMATIC STUDY OF FIELD OATHS IN DIFFERENT LINGUISTIC-CULTURAL ENVIRONMENTS - Saminjonov Mukhammadali (Journals Park Publishing, 2022)
The article describes the application of the linguistic and cultural system, the foundations of linguistics, and the environment of the linguistic and cultural sphere.
Keywords: language, linguistics, linguistic culture, environment, field